The Australian aboriginal - Basedow, Herbert, 1881-1933 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Australian Aboriginal" by Herbert Basedow is a scientific publication written in the early 20th century. This work provides a comprehensive examination of the physical, cultural, and ethnological aspects of Indigenous Australian peoples. Basedow, a prominent figure in Australian anthropology and a former protector of Aborigines, draws on a wealth of firsthand observations from his many expeditions across central and northern Australia to contribute valuable insights into Aboriginal life and practices. The opening of the book serves as an introduction to the Australian Aboriginal tribes, setting the stage for the author's exploration of their lives and customs. Basedow describes a moment of initial contact between a group of travelers and an Aboriginal tribe, capturing the cautious yet curious interactions that unfold. Through vivid imagery, he paints a scene of a remote landscape filled with suspense as the travelers encounter the melodic call of the indigenous people, leading to a formal introduction marked by mutual gestures of friendliness. This beginning establishes an intimate tone, highlighting the author's appreciation for the Aboriginal way of life, which he aims to document and analyze throughout the text. (This is an automatically generated summary.)
Release date is 2023-10-23
Tim Lindell and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Ethnology -- Australia; Aboriginal Australians